An environment-friendly modified ABS roadia hard bait bionics material, a forming process and a roadia hard bait

CN122917481APending Publication Date: 2026-10-16观乐户外用品(威海)有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611341376.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]在硬饵的成型工艺也存在内在矛盾,微发泡注射成型虽可减重10%–30%,但常规发泡注塑在制品表面易产生流痕、银纹与微孔缺陷,破坏饵体表面的光洁度,这直接导致涂装附着力不足、泳姿仿真度下降;另一方面,回收ABS(rABS)因来源波动或批次不稳定,缺乏针对性的工艺手段,难以保证饵体批量一致性,制约了回收料在高端渔具上的应用

Benefits of technology

[0020] In terms of weather resistance, the formula incorporates hindered amine light stabilizers and UV absorbers to form a composite anti-aging system. Under repeated sun exposure and immersion conditions, the material can maintain color stability for a long time, and is not prone to yellowing or chalking, thus ensuring the swimming stability of the bait and the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917481A_ABST
    Figure CN122917481A_ABST
Patent Text Reader

Abstract

This invention discloses an environmentally friendly modified ABS biomimetic material for lure hard baits, a molding process, and the resulting lure hard bait, belonging to the field of polymer materials and fishing gear manufacturing. The material, by weight, comprises: 40-70 parts recycled ABS, 5-20 parts bio-based biodegradable toughening components, 2-8 parts compatibilizer, 1-30 parts density adjusting components, and 0.5-3 parts weather-resistant stabilizing system, with an overall density of 0.80-1.40 g / cm³. The molding process involves melt blending and granulation followed by injection molding. The surface temperature of the mold cavity is controlled in stages, and gas back pressure is applied to form a dense skin-core structure with a foamed core layer, resulting in a weight reduction of 10%-25%. The density of the produced lure hard bait is continuously adjustable within the range of 0.80-1.40 g / cm³, with a Shore D hardness of 55-75, a cantilever beam notched impact strength ≥8 kJ / m², and no internal lead weight. Using recycled ABS and bio-based biodegradable materials as the base, and achieving a lead-free design that floats / suspends / sinks through density adjustment, combined with environmentally friendly coating, it has good mechanical properties, weather resistance and fish attraction function, solving the problem of the difficulty in balancing environmental protection and performance of existing lure hard baits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polymer material and a fishing tackle manufacturing process, and more particularly to an environmentally friendly modified ABS biomimetic material for lure hard baits, a molding process, and a lure hard bait. Background Technology

[0002] Hard lures used in lure fishing are usually injection molded, with common materials including ABS, PVC, polyurethane resin, and balsa wood (light wood), with ABS being the most common. Hard lures float, suspend, or sink in still water and produce specific swimming actions when pulled, such as swaying, trembling, or rolling. In terms of attracting fish, they use paint, realistic shapes, and simulated movements to lure predatory fish. At the same time, the lure body must withstand repeated casting, fish bites, water erosion, and temperature changes to maintain its shape and swimming action stability.

[0003] Traditional ABS is non-degradable, posing a significant environmental challenge. Hard baits easily remain in rivers, lakes, and seas after line breakage, hook loss, or accidental casting, causing persistent plastic pollution. Therefore, recyclable and biodegradable alternatives to hard baits have become a clear industry trend. However, biodegradable substrates (such as PHA, PLA, and PBAT) generally suffer from insufficient toughness, high cost, or difficulty in controlling degradation rates. Regarding fish-attracting functions, the compatibility, durability, and slow-release rate of fish-attracting functions such as fluorescence, light storage, reflection, and slow-release odors with environmentally friendly substrates lack research. Furthermore, while microfoaming can reduce material usage and density, the impact of cell structure on fluorescence brightness and coating adhesion has not been systematically reported, making it difficult to achieve both environmental friendliness and fish-attracting performance. Therefore, current hard bait buoyancy relies on lead weighting, but lead toxicity and its leaching risk in the aquatic environment are increasingly criticized. Existing technological improvements often use stainless steel, zinc alloys, or tungsten weighting, but this significantly increases costs and remains a partial replacement approach.

[0004] There are inherent contradictions in the molding process of hard baits. Although micro-foaming injection molding can reduce weight by 10%–30%, conventional foaming injection molding is prone to producing flow marks, silver streaks and micropore defects on the surface of the product, which damages the smoothness of the bait surface. This directly leads to insufficient coating adhesion and reduced swimming posture simulation. On the other hand, recycled ABS (rABS) is subject to fluctuations in source or unstable batches, and lacks targeted processing methods, making it difficult to ensure batch consistency of baits and restricting the application of recycled materials in high-end fishing gear.

[0005] In conclusion, there is a lack of end-to-end environmental protection solutions that can achieve a balance between environmental protection and performance. Summary of the Invention

[0006] To address the shortcomings of the aforementioned technologies, this invention provides an environmentally friendly modified ABS biomimetic material for lure hard baits, a molding process, and lure hard baits.

[0007] To solve the above technical problems, the technical solution adopted by the present invention is: an environmentally friendly modified ABS lure hard bait biomimetic material, comprising, by weight: Recycle 40-70 parts of ABS; 5-20 parts of bio-based biodegradable toughening components; Compatibilizer 2-8 parts; Density adjustment component: 1-30 parts; 0.5-3 parts of weather-resistant stabilizing system; The overall density of the environmentally friendly modified ABS lure hard bait biomimetic material is 0.80-1.40 g / cm³.

[0008] Furthermore, the bio-based degradable toughening component is at least one of PHA, PBAT, or PLA graft copolymer.

[0009] Furthermore, the density adjusting component includes at least one of the following: 1-15 parts of hollow glass microspheres with a true density of 0.2-0.6 g / cm³, 0.5-3 parts of chemical foaming agent, and 5-30 parts of heavy filler with a true density greater than 2.5 g / cm³.

[0010] Furthermore, the weather-stabilized system includes 0.3-2 parts of hindered amine light stabilizer and 0.2-1 parts of UV absorber.

[0011] Furthermore, it also contains 0.5-5 parts of fluorescent / phosphorescent pigment and / or 1-5 parts of odor-sustaining microcapsules.

[0012] A molding process for environmentally friendly modified ABS lure hard bait includes: melting, blending, granulating, and then injection molding the components of the environmentally friendly modified ABS lure hard bait biomimetic material. During injection molding, the surface temperature of the mold cavity is controlled in steps of 40-60℃. Optionally, after mold closing, a gas back pressure of 0.5-5MPa is applied to the mold cavity to form a skin-core structure with a dense skin layer and a foamed core layer, resulting in an overall weight reduction of 10%-25%.

[0013] Furthermore, the injection barrel temperature is 200-230℃, and the nozzle section temperature is 5-10℃ lower than the previous section; the injection speed adopts a slow-fast-slow stage; the holding pressure is 40-80MPa, and the holding time is 3-8s.

[0014] Furthermore, the coating includes post-molding environmentally friendly coating, which involves pre-treating the dense skin layer and then spraying a water-based UV-curing primer and a bio-based polyurethane topcoat. The coating has near-zero VOC and cross-cut adhesion ≥ level 1.

[0015] A type of lure, made from environmentally friendly modified ABS lure biomimetic material or by the molding process of environmentally friendly modified ABS lure, has an overall density of 0.80-1.40 g / cm³, a Shore D hardness of 55-75, a cantilever beam notched impact strength ≥8 kJ / m², and contains no lead weight inside.

[0016] Furthermore, hard lures for lure fishing can be any one of the following: floating type with an overall density of 0.85-1.00 g / cm³, suspended type with an overall density of 0.98-1.02 g / cm³, or sinking type with an overall density of 1.05-1.40 g / cm³.

[0017] This invention relates to an environmentally friendly modified ABS lure biomimetic material, molding process, and lure. The technical solution uses recycled ABS as the base resin, compounded with bio-based biodegradable toughening components such as PHA and PBAT, and introduces compatibilizers to form an in-situ island structure or bicontinuous structure in the blend system. This structural design compensates for the insufficient toughness of the biodegradable components themselves and also improves the impact performance degradation problem caused by repeated processing of recycled ABS. After use, the surface polyester phase of the waste lure preferentially undergoes hydrolysis or microbial erosion, giving the material controllable degradation capabilities.

[0018] In terms of density control, the formula incorporates hollow glass microspheres, chemical foaming agents, and heavy fillers to form a density adjustment system. Based on the mass-weighted mixing density formula, the density can be continuously adjusted within the range of 0.80~1.40 g / cm³, allowing the lure's floating, suspended, and sinking states to be directly determined by the formula, eliminating the need for added lead weights and thus avoiding the environmental and health risks associated with lead leaching.

[0019] To address common surface defects in microfoam injection molding, this solution employs stepped temperature control of the mold cavity surface and gas backpressure-assisted injection molding to create a core-skin structure that combines a dense outer layer with a foamed core layer. This structure reduces overall weight by 10%–25% while maintaining a smooth and even surface, effectively improving coating adhesion. The accompanying coating system uses a water-based UV-curing primer and a bio-based polyurethane topcoat, achieving a near-zero VOC emission environmentally friendly coating process.

[0020] In terms of weather resistance, the formula incorporates hindered amine light stabilizers and UV absorbers to form a composite anti-aging system. Under repeated sun exposure and immersion conditions, the material can maintain color stability for a long time, and is not prone to yellowing or chalking, thus ensuring the swimming stability of the bait and the service life of the coating. Attached Figure Description

[0021] Figure 1 This is the afterglow decay curve of the photoluminescence of the present invention.

[0022] Figure 2This is a schematic view of the rear structure of the present invention. Detailed Implementation

[0023] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0024] Example 1:

[0025] Environmentally friendly modified ABS biomimetic material for lure hard baits, designed to create floating hard baits, employs a combination of microbeads and foaming for weight reduction.

[0026] The specific formulation of this embodiment is as follows: 55 parts of recycled ABS (rABS), 12 parts of PBAT (polybutylene adipate / terephthalate), 4 parts of ABS-g-MAH (maleic anhydride grafted ABS resin), 8 parts of hollow glass microspheres (true density 0.45 g / cm³, particle size 30μm), 1.0 part of AC foaming agent (with 0.3 parts of ZnO activator), 0.8 parts of HALS-770 (light stabilizer 770), 0.5 parts of UV-326, 0.6 parts of antioxidant 1010 / 168 (1:1), 1.0 part of lubricant EBS, and 2 parts of phosphorescent pigment (strontium aluminate: Eu, Dy); Molding involves granulation at 190℃ using a twin-screw extruder, followed by drying at 85℃ for 3 hours; injection molding is performed at a material temperature of 210℃ (nozzle 205℃), a mold cavity surface temperature of 45℃, with slow-fast-slow injection, a gas back pressure of 2MPa, a holding pressure of 60MPa / 5 s, and a cooling time of 20 s; water-based UV primer and bio-based PU topcoat are also used. The overall density is 0.92 g / cm³, with a weight reduction of 18%. The notched impact strength of the cantilever beam is 9.5 kJ / m², the color difference ΔE=1.8 in QUV 500 h, and the cross-cut adhesion is grade 1. When placed in fresh water, it floats. The measured amplitude of the traction swimming posture is better than that of the lead-weighted control sample, and the light storage time is >8 h.

[0027] Example 2:

[0028] Environmentally friendly modified ABS biomimetic material for lure hard baits, designed to form suspended hard baits, uses a combination of microbeads and heavy calcium carbonate.

[0029] The specific formula is as follows: 50 parts rABS, 15 parts PHA (polyhydroxyalkanoate), 5 parts SEBS-g-MAH (maleic anhydride grafted SEBS), 10 parts hollow glass microspheres, 8 parts heavy calcium carbonate (D50=8μm), 1.0 part HALS-944 (polymerized hindered amine light stabilizer), 0.5 parts UV-328, 0.6 parts antioxidant, 1.2 parts lubricant, and 3 parts odor-sustaining microcapsules (starch wall material / fish meal core material). The molding process is the same as in Example 1, with a gas back pressure of 3 MPa and a holding pressure of 55 MPa. It forms an overall density of 1.00 g / cm³, a static water suspension time of >60 s, an odor slow-release period of about 60 days, a notched impact strength of 8.8 kJ / m², and an adhesion rating of 1.

[0030] Example 3:

[0031] Environmentally friendly modified ABS lure biomimetic material, designed for both sinking hard lures and heavy filler hard lures.

[0032] The specific formula is as follows: 60 parts rABS, 8 parts PBAT, 3 parts ABS-g-MAH, 25 parts barium sulfate (D50=5 μm), 0.8 parts HALS-770, 0.5 parts UV-326, 0.6 parts antioxidant, and 1.0 part lubricant; The molding process is the same as in Example 1, but without foaming agent, without gas back pressure, and with a material temperature of 220°C. It forms an overall density of 1.25 g / cm³, a settling rate of 0.8–1.2 m / s (adjustable by the amount of barium sulfate used), a notched impact strength of 9.0 kJ / m², and an adhesion rating of Grade 1.

[0033] Example 4:

[0034] Environmentally friendly modified ABS biomimetic material for lure hard baits, targeting hard baits with economical content.

[0035] The specific formula is as follows: 68 parts rABS, 6 parts PBAT, 2 parts ABS-g-MAH, 0.8 parts AC foaming agent, 0.5 parts HALS-770, 0.3 parts UV-326, 0.4 parts antioxidant, 0.8 parts lubricant, and 3 parts black masterbatch; The molding process is the same as in Example 1, with a mold cavity surface temperature of 50°C and a back pressure of 1 MPa. The overall density is 0.98 g / cm³ (suspended and partially buoyant), the weight is reduced by 15%, the notched impact strength is 8.2 kJ / m², the proportion of recovered components is >65%, and the cost is reduced by about 15% compared with Example 1.

[0036] Comparative Examples

[0037] Commercially available general-purpose ABS, lead weighting, and solvent-based coating.

[0038] The formula is 100 parts of general-purpose petroleum-based ABS, conventional injection molding, lead weighting in the abdominal area, and solvent-based nitrocellulose lacquer coating. Overall density 1.05 g / cm³ (sinks only, floats and sinks are not adjustable), non-degradable, QUV 500 h color difference ΔE=5.2, high VOC coating, adhesion grade 2, lead weighting poses a risk of leaching.

[0039] Performance summary table of each embodiment and comparative embodiment

[0040] In the above embodiments, the interaction mechanisms between the components are as follows: Between the recycled ABS matrix and the bio-based toughening components, rABS undergoes thermo-oxidative aging during recycling, leading to cross-linking or chain breakage of the butadiene phase, which reduces its impact toughness. In contrast, flexible polyesters such as PHA and PBAT have low melting points and good flexibility. By using compatibilizers to form island structures or bicontinuous structures in situ, they can simultaneously achieve toughening and introduce degradation initiation points. When the bait is discarded, if the surface polyester phase is hydrolyzed or eroded by microorganisms, it will form surface roughening, accelerating the overall disintegration and degradation. Together, these two factors enable the material to simultaneously meet the requirements of high performance during its service life and degradability after disposal.

[0041] Between density adjustment components and buoyancy design, hollow glass microspheres are used. These are low-density rigid microspheres that can significantly reduce density. Chemical foaming agents create micropores, further reducing density and providing foam-like buoyancy. Note that over-foaming can damage the surface. Heavy fillers (calcium carbonate and barium sulfate) increase density and improve the casting weight and sinking speed of hard baits. Therefore, by combining these three components in the target density ratio (based on the mixed density weighting formula ρ=Σ(wᵢ / ρᵢ)⁻¹), the density can be continuously adjusted within the range of 0.80-1.40 g / cm³. This allows the formula density to replace lead weighting, achieving lead-free buoyancy control. Specifically, the density design method is demonstrated based on the floating formulation of Example 1. The target overall density is set to ρ0 = 0.92 g / cm³, and the mass fraction and true density of each component are as follows: rABS (w = 0.55, ρ = 1.05), PBAT (w = 0.12, ρ = 1.26), ABS-g-MAH (w = 0.04, ρ = 1.04), hollow glass microspheres (w = 0.08, ρ = 0.45), phosphorescent pigments and other components (total w = 0.21, approximately ρ = 1.10). The density was calculated using the mixed density weighted formula ρ0=1 / Σ(wᵢ / ρᵢ): 0.55 / 1.05+0.12 / 1.26+0.04 / 1.04+0.08 / 0.45+0.21 / 1.10≈0.524+0.095+0.038+0.178+0.191=1.026, yielding a theoretical density of approximately 0.975 g / cm³, higher than the target value. By increasing the microbead dosage to 10 parts (w≈0.10) and introducing 1 part of AC foaming agent (the equivalent volume expansion after foaming is approximately 15%, meaning the equivalent density contribution is calculated at 0.85), the theoretical density was recalculated to be approximately 0.91-0.93 g / cm³, consistent with the measured value of 0.92 g / cm³ for the small sample. Similarly, the sinking type (Example 3) achieves a theoretical density of approximately 1.24 g / cm³ and a measured density of 1.25 g / cm³ by setting the barium sulfate dosage to 25 parts (w=0.25, ρ=4.4) and eliminating foaming. Thus, the bait density can be engineered within the range of 0.80-1.40 g / cm³ based on the mass fraction and true density of the formulation components. The floating, suspended, and sinking states can be designed according to the target swimming posture, eliminating the need for lead weighting.

[0042] HALS inhibits ABS photo-oxidation by capturing free radicals and regenerating the cycle, while UV absorbers shield ultraviolet rays. The combination of these two methods produces an anti-aging effect, ensuring that the bait does not yellow or powder under repeated sun exposure and soaking conditions, thereby maintaining its swimming posture and coating life.

[0043] The skin-core structure, along with coating / weight reduction, mold temperature gradient, and gas back pressure, jointly suppress surface foaming, forming a dense skin layer. This ensures a smooth bait surface and provides a complete adhesion substrate for the coating. Core layer foaming can achieve a weight reduction of 10%-25%, reducing material usage.

[0044] The density-impact-weather resistance full factorial orthogonal test and variance analysis tables for each embodiment have been verified; details are as follows: Density-Impact-Weather Resistance Full Factor Orthogonal Test (L9(3)) 4 (×2 repeated)

[0045] 1.1 Factors and Levels

[0046] 1.2 Experimental design and results (2 replicates, 18 groups in total)

[0047] Response indicators: density ρ (g / cm³); notched impact strength of cantilever beam (kJ / m²); QUV 500 h color difference ΔE.

[0048] 1.3 Range analysis (the larger the R value, the more significant the impact)

[0049] Density ρ (g / cm³); Order of importance: C>A>B>D (heavy fillers have the greatest impact on density, followed by hollow microspheres, while HALS has no significant impact). Impact strength (kJ / m²);

[0050] Order of importance: A > B > D > C; QUV 500 h color difference ΔE;

[0051] Priority order: D > A > B > C (HALS plays a decisive role in weather resistance); Analysis of variance (ANOVA, α=0.05 / 0.01, F-critical value F0). 05 (2,9)=4.26, F0. 01 (2,9)=8.02); Response 1: Density ρ;

[0052] Response 2: Impact strength (kJ / m²);

[0053] Response 3: QUV 500 h color difference ΔE; (Note: * indicates P < 0.05 is significant, ** indicates P < 0.01 is highly significant; blank lines indicate no significance)

[0054] The conclusions of the orthogonal experiment are as follows: 1. Density programmability verification: C (heavy filler) and A (microspheres) were both highly significant (P<0.01), verifying the feasibility of replacing lead weight with density in the formulation; HALS had no significant effect on density (can be optimized independently).

[0055] 2. Toughness-weight reduction trade-off; B (foaming agent) has a significant impact on the loss of impact strength. It is recommended to control the amount of foaming agent at 0.5-1.0 parts and use a skin-core structure (dense skin layer for load bearing) to compensate; the density / toughness balance point is around 10 parts of microspheres.

[0056] 3. Weather resistance optimization; HALS was a highly significant factor (P<0.01), and 1.0-1.5 parts can meet the target of QUV 500 h ΔE≤3 (ΔE < 2.2 for each combination).

[0057] 4. Recommended optimized combinations: Floating type A2B1C1D2 (microbeads 10, AC 0.5, heavy calcium carbonate 0, HALS 1.0); Suspended type A2B2C2D2; Submerged type A1B1C3D2.

[0058] like Figure 1 As shown, in conjunction with the above Example 1, we verified the afterglow decay curve (strontium aluminate: Eu, Dy, after 10 min 365nm excitation); The attenuation model adopts the triple-exponential attenuation equation commonly used for photoluminescent materials: I(t) = I0·(0.35·e^(−t / 40) + 0.35·e^(−t / 400) + 0.30·e^(−t / 2000)), I0= 3000mcd / m²;

[0059] In addition, fluorescence brightness (relative brightness decay under continuous UV-A irradiation, 8 h) was verified; F(h) = 100·(0.90 + 0.10·e^(−h / 6));

[0060] The quantum efficiency of the fluorescent pigment decays slowly under continuous UV irradiation, remaining at approximately 92% after 8 hours, which meets the requirements for multiple applications during the day.

[0061] Furthermore, considering the release curve of the odor-sustaining microcapsules in Example 2, such as... Figure 2 As shown;

[0062] The release model adopts the Korsmeyer-Peppas equation for Fickian diffusion in a spherical matrix: M(t) / M∞ = k·tⁿ, n = 0.45 (Fickian), k = 0.147.

[0063] It can be seen that approximately 15% (surface core material) is released initially, followed by a near-zero slow-release platform, with a cumulative release of approximately 93% over 60 days, meeting the initial needs for rapid attraction and continuous slow-release fish attraction.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] By combining hollow microspheres, foaming agents and heavy fillers, the density of the material body can be continuously adjusted from 0.80 to 1.40 g / cm³, so that the three states of floating, suspended and sinking are directly determined by the formula. This eliminates the need for lead counterweights, eliminates the environmental and health risks of lead use, and also eliminates the quality hazards of loose counterweights falling off.

[0066] Fluorescent / photoluminescent pigments, odor-slow-release microcapsules, and environmentally friendly substrates are compatible, allowing for adjustable cell and filler distribution. This achieves both environmental friendliness and fish-attracting performance, overcoming the problem of limited functionality in existing biodegradable baits.

[0067] Temperature-gradient gas back pressure in the mold enables a structure with a dense skin and a foamed core, reducing weight by 10%-25% while ensuring a smooth surface and good coating adhesion; the water-based UV and bio-based PU coatings have near-zero VOCs.

[0068] The base material is made of recycled ABS, realizing the recycling of waste plastics; it is supplemented with bio-based biodegradable components such as PHA and PBAT, giving the material some biodegradability; with recycled ABS as the main body and the amount of bio-based components controlled at 5-20 parts, it balances performance, environmental protection and cost, and has the feasibility of large-scale promotion.

[0069] It should be noted that the materials and processes of this invention have reached the pilot-scale feasibility stage. The twin-screw compounding and granulation, injection molding, gas back pressure control, and water-based coating are all mature and universal equipment, and no new special equipment is required. rABS can be obtained from sources such as household appliance dismantling materials and electronic appliance recycling materials.

[0070] The above embodiments are not intended to limit the present invention, and the present invention is not limited to the examples given above. Any changes, modifications, additions or substitutions made by those skilled in the art within the scope of the technical solution of the present invention are also within the protection scope of the present invention.

Claims

1. An environmentally friendly modified ABS biomimetic material for hard lures, characterized in that, Included by weight parts: Recycle 40-70 parts of ABS; 5-20 parts of bio-based biodegradable toughening components; Compatibilizer 2-8 parts; Density adjustment component: 1-30 parts; 0.5-3 parts of weather-resistant stabilizing system; The overall density of the environmentally friendly modified ABS lure biomimetic material is 0.80-1.40 g / cm³.

2. The environmentally friendly modified ABS hard lure biomimetic material according to claim 1, characterized in that: The bio-based biodegradable toughening component is at least one of PHA, PBAT, or PLA graft copolymer.

3. The environmentally friendly modified ABS hard lure biomimetic material according to claim 1, characterized in that: The density-adjusting component includes at least one of the following: 1-15 parts of hollow glass microspheres with a true density of 0.2-0.6 g / cm³, 0.5-3 parts of chemical foaming agent, and 5-30 parts of heavy filler with a true density greater than 2.5 g / cm³.

4. The environmentally friendly modified ABS hard lure biomimetic material according to claim 1, characterized in that: The weather-resistant stabilizing system comprises 0.3-2 parts of hindered amine light stabilizer and 0.2-1 parts of UV absorber.

5. The environmentally friendly modified ABS hard lure biomimetic material according to any one of claims 1-4, characterized in that: It also contains 0.5-5 parts of fluorescent / phosphorescent pigment and / or 1-5 parts of odor-sustaining microcapsules.

6. A molding process for environmentally friendly modified ABS hard lures, characterized in that, include: The components of the material described in any one of claims 1-5 are melt-blended, granulated, and then injection molded. During injection molding, the surface temperature of the mold cavity is controlled in steps of 40-60°C. Optionally, after mold closing, a gas back pressure of 0.5-5MPa is applied to the mold cavity to form a skin-core structure with a dense skin layer and a foamed core layer, resulting in an overall weight reduction of 10%-25%.

7. The molding process for the environmentally friendly modified ABS hard lure according to claim 6, characterized in that, The injection barrel temperature is 200-230℃, and the nozzle section temperature is 5-10℃ lower than the previous section; the injection speed adopts a slow-fast-slow stepwise approach; the holding pressure is 40-80MPa, and the holding time is 3-8s.

8. The molding process for the environmentally friendly modified ABS hard lure according to claim 7, characterized in that, The coating includes post-molding environmentally friendly coating, which involves spraying a water-based UV-curing primer and a bio-based polyurethane topcoat after pre-treating the dense skin layer. The coating has near-zero VOC and cross-cut adhesion ≥ level 1.

9. A hard lure for lure fishing, characterized in that, Prepared from the material described in any one of claims 1-5 or the process described in any one of claims 6-8, the lure has an overall density of 0.80-1.40 g / cm³, a Shore D hardness of 55-75, a cantilever beam notched impact strength ≥8 kJ / m², and contains no lead weight.

10. The hard lure according to claim 9, characterized in that, The hard lure is any one of the following: floating type with an overall density of 0.85-1.00 g / cm³, suspended type with an overall density of 0.98-1.02 g / cm³, or sinking type with an overall density of 1.05-1.40 g / cm³.